Automatic Skull Stripping of Rat and Mouse Brain MRI Data Using U-Net - Hsu, Li-Ming; Wang, Shuai; Ranadive, Paridhi; Ban, Woomi; Chao, Tzu-Hao Harry; Song, Sheng; Cerri, Domenic Hayden; Walton, Lindsay R.; Broadwater, Margaret A.; Lee, Sung-Ho; Shen, Dinggang; Shih, Yen-Yu Ian (Frontiers in Neuroscience, 2020)
Accurate removal of magnetic resonance imaging (MRI) signal outside the brain, a.k.a., skull stripping, is a key step in the image pre-processing pipeline. In rodents, this is mostly achieved by manually editing a brain mask, which is time-consuming and operator dependent. Automating this step is particularly challenging in rodents as compared to humans because of differences in brain/scalp tissue geometry, image resolution with respect to brain-scalp distance, and tissue contrast around the skull. In this study, we proposed a deep-learning-based framework, U-Net, to automatically identify the rodent brain boundaries in MR images. The U-Net method is robust against inter-subject variability and eliminates operator dependence. To benchmark the efficiency of this method, we trained and validated our model using in-house collected and publicly available datasets. In comparison to current state-of-the-art methods, our approach achieved averaged Dice similarity coefficients of 0.97 on T2-weighted anatomical images, and 0.96 on T2*-weighted echo planar imaging, demonstrating robust performance of our approach across various MRI protocols.